Conceptual Principles of Regional Education Policy: monograph - Pryima, Serhii; Прийма, Сергій Миколайович; Прийма, Сергей Николаевич (My University, 2018)
The monograph describes the conceptual foundations of regional educational policy, objectified in the theoretical description of the main approaches, principles, conditions to implement the lifelong learning concept as a factor of regional development. The basic prerequisites for the development of lifelong learning concept in the world and the socio-economic results of its implementation are analyzed. The peculiarities and specifics of lifelong learning, education of adults as a part of it in the conditions of regional development (national and foreign experience) are described. The psychological peculiarities of personality development in adulthood as well as professional development of personality at different stages of adolescence are characterized. The role of non-formal adults education as a factor of learning regions development as well as mechanisms of the city development and implementation of the concept is highlighted. The results of sociological research of cultural and educational needs of Zaporizhzhya region's residents and their level of satisfaction are interpreted.
Keywords: regional educational policy; education